Production Analysis of Horizontal Wells in a Two-Region Composite Reservoir Considering Formation Damage - Li, Jingsong; Wang, Tao (Frontiers in Energy Research, 2022)
The horizontal well is extensively used to exploit oil at the Bohai offshore oilfield, China. It has been proved by practice that formation damage always happens during the production of wells. However, it is a challenging task to evaluate the formation damage for horizontal wells. In this paper, a flow model considering formation damage is established for horizontal wells. The reservoir geometry is divided into two regions: the inner region represents the region of formation damage and the outer region that without damage. The finite element method is used to solve the flow model. The well production rate can be determined by using the material balance method. For different scenarios, such as when the horizontal well is completely in the inner region or when the horizontal well passes through two regions, the effects of some key parameters such as damage radius, damage region permeability, and well position on the oil production rate and pressure distribution characteristics are analyzed. The results show that a smaller damage radius, higher damage zone permeability, and a horizontal well closer to or in greater contact with the outer region result in a higher oil production rate and faster pressure drop propagation. The presented model and obtained results enrich production analysis of horizontal wells in a two-region composite reservoir considering formation damage, which has significance for efficient offshore reservoir development.